Comparison of the superconducting rectangular critical fields with the same area at κ = 1.5 - Fuad Anwar; C Cari; Alqaan Maqbullah Ilmi (Journal of Physics: Theories and Applications, 2019)
The Time Dependent Ginzburg-Landau (TDGL) equation can be used to study the characteristics of superconductors in the evolution of time to reach equilibrium. This study uses the ѰU method to numerically calculate critical field values more easily. Previous research has been carried out on size variations, kappa variations, proximity effects and so on. In this study, a comparison between squares and rectangles with the same size of area for type II superconductor , then it is found that the critical field Hc3 is the same value for each of the same area.